Global deterioration of cardiovascular mechanics by carfilzomib treatment is associated with proteasome activity in patients with relapsed multiple myeloma. (14th October 2021) - Makris, N; Laina, A; Georgiopoulos, G; Gavriatopoulou, M; Papanagnou, E.D; Eleutherakis-Papaiakovou, E; Fotiou, D; Dialoupi, I; Migkou, M; Roussou, M; Terpos, E; Trougakos, I.P; et al.
Abstract: Background: Carfilzomib (CFZ) is a second generation irreversible proteasome inhibitor that has been shown to improve overall survival in patients with relapsed or refractory multiple myeloma (MM) but is associated with cardiac toxicity in MM. Because ubiquitin-proteasome system (UPS) is involved in cardiovascular homeostasis exploring the effects of proteasome inhibition on cardiac mechanics, in a clinical setting, would provide novel insight of the clinical role of UPS in cardiovascular disease. Aim: To gain a thorough understanding of proteasome inhibition on myocardial mechanics in a clinical setting. Methods: We prospectively evaluated 48 patients with relapsed or refractory MM and an indication to receive CFZ treatment [median age: 67.5, interquartile range (64–73), 66.7% men]. All patients underwent cardiac ultrasonography at an initial visit, at the first day of the 3rd month (C3D1, n=25) and at the last day of cycle 6 (C6D16, n=48). Pulse wave velocity (PWV) was used to assess arterial stiffness and calculate arterial-ventricular coupling (VAC) by the ratio (PWV/global longitudinal strain (GLS)). Carfilzomib was administered at 27mg/m 2 on days 1 (C1D1) and 2 (C1D2) of cycle 1 and at 56mg/m 2 thereafter. Blood was drawn at baseline, C3D1 and C6D16 to measure proteasome activity (PrA). Patients were followed up for carfilzomib–related cardiovascular adverse events. Results: Regarding systolic function, between baseline and C6D16, we noticed deterioration in left ventricular ejection fraction (LVEF) (57.7±5.4% vs 56.1±7.19%, p=0.022), GLS (−20.51±2.78 vs −18.88±3.45%, p=0.003), S wave of LV longitudinal strain rate and radial strain (p<0.05 for both). Markers of LV diastolic function also deteriorated at 6 months including early diastolic (Ea) mitral annular velocity (7.27±1.83cm/sec vs 6.7±1.64cm/sec, p=0.008) and E wave of LV longitudinal strain rate (1.1±0.37sec-1 vs 0.95±0.36sec-1, p=0.010). Left atrial volume (LAV) and index (LAVi) increased both at 3 and 6 months (p<0.05). Peak LA strain at reservoir phase (peak atrial longitudinal strain, PALS) was also decreased at 6th and 3rd month measurements (p<0.05), whereas LA strain rate at reservoir function (s wave) was decreased, compared to baseline, only at 6th month (p=0.001). RV longitudinal strain also decreased between 3rd and 6th month (p=0.039). Furthermore, PWV/GLS also deteriorated at 6 months (−0.56±0.13 vs −0.64±0.21, p=0.001). By linear mixed models analysis, we found that changes in proteasome activity were associated with changes in PWV/GLS (p=0.017), LAV (p=0.015) and LAVi (p=0.009), and PALS (p=0.014). Conclusion: CFZ treatment was associated with global deterioration of markers of myocardial systolic and diastolic function and VAC. The observed association of changes in proteasome activity with VAC and left atrial function and structure supports a direct effect of proteasome inhibition on the cross-talk between LV and arterial function and LV diastolic function. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amgen